Evaluating English coursebooks for Indonesian vocational schools: A SQRAR-based material analysis in the EFL context - Sukarno Sukarno; Ari Purnawan; Megan Jinabe (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2025)
English learning materials play a pivotal role in supporting vocational high school (SMK) students in acquiring language competencies relevant to both academic progression and workplace demands. This study evaluates the quality, relevance, and pedagogical suitability of government-issued English coursebooks for Grades 10, 11, and 12 used in Indonesian vocational schools. Employing the SQRAR (Structure, Quality, Relevance, Appropriateness, and Readability) evaluation framework, expert reviewers in English language teaching assessed the coursebooks based on content organization, contextual alignment, linguistic features, and usability. The findings show that while the materials generally align with the national curriculum, several aspects require enhancement—particularly in integrating vocationally contextualized content, improving readability, and strengthening task authenticity. The study highlights the need for systematic revisions and adaptive learning resources that better reflect the linguistic, professional, and communicative needs of vocational students. Recommendations include embedding workplace discourse, incorporating industry-relevant tasks, and enriching multimodal resources to ensure that English materials more effectively support students’ future employability in diverse vocational fields.